Neuroendocrine cell populations in normal human lungs: a quantitative study. - Gosney, J R (1988)
Pulmonary neuroendocrine cells, identified by their positive immunochemical reaction for neurone specific enolase, were readily demonstrable and uniformly distributed in 15 pairs of normal adult human lungs. About 65% contained gastrin releasing peptide and nearly all the rest contained calcitonin. Leucine-enkephalin was not found. Serotonin containing cells were few, and cells immunoreactive for adrenocorticotrophin and antidiuretic hormone were absent. About one in 10 cells was argyrophilic, and costorage of peptides was not seen.